Europeana: Aggregating Cultural Diversity In Unity - Syifa Adiba; Febriyanto Febriyanto (Universitas Khairun, 2021)
This study examines Europeana, a European cultural heritage data aggregator. The purpose of this study is to explore the Europeana platform and its relationship in a broader field. The purpose of this research is to provide an overview of Europeana development and demonstrate the significant alteration in the platform. A qualitative approach used in this study is descriptive methods and direct observation to Europeana website, alongside with literature review was conducted for the data retrieval technique. The research found that Europeana experienced a significance in the development and has several objectives, but more importantly emphasized more on creation, production and distribution process of digital heritage content in Europe. As a result, Europeana has a significant effect on cultural heritage sustainability through work closely with digitization to present the tacit knowledge in the public sphere and preserve cultural heritage object.